Multicultural Education and Communication Competences of the Pupils in a Multiethnic Classroom in the Czech Republic - Jaromira Sindelarova (Communications - Scientific letters of the University of Zilina, 2007)
In accordance with new principles of curricular policy formulated in the National Program of Development of Education in the Czech Republic in 2004 the new system of curricular documents for education of pupils from three to nineteen years of age is given. The aim of the article is to describe general situation with this related and outline main tasks which wait the Czech educational system in the connection with these problems in immediate future.